2016
DOI: 10.5056/jnm15182
|View full text |Cite
|
Sign up to set email alerts
|

Role of Mixed Reflux and Hypomotility with Delayed Reflux Clearance in Patients with Non-cardiac Chest Pain

Abstract: Background/AimsGastroesophageal reflux disease (GERD) is the most common cause of non-cardiac chest pain (NCCP). Currently available data reveal a weak relationship between NCCP and dysmotility. Moreover, it is unclear why some refluxes are perceived as heartburn and others as NCCP. We aimed to evaluate the role of the reflux pattern and the esophageal motility in patients with NCCP. MethodsForty-eight patients with NCCP (Group 1) and 50 only typical GERD symptoms (Group 2) were included and underwent highreso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 29 publications
0
10
0
1
Order By: Relevance
“…The likelihood of a normal HRM study is less when esophageal reflux burden is high, and even lower when erosive esophagitis or Barrett's esophagus are diagnosed . The most common abnormal pattern in GERD is hypomotility, of the esophageal body, the LES, or both .…”
Section: Resultsmentioning
confidence: 99%
“…The likelihood of a normal HRM study is less when esophageal reflux burden is high, and even lower when erosive esophagitis or Barrett's esophagus are diagnosed . The most common abnormal pattern in GERD is hypomotility, of the esophageal body, the LES, or both .…”
Section: Resultsmentioning
confidence: 99%
“…For those who were resistant to PPI therapy, Tsutsui et al (8) reported a prevalence of abnormal esophageal motility of 47.9%. However, in the study by Ribolsi et al (9), only 24% of patients with typical GERD symptoms demonstrated esophageal dysmotility. In our study, the prevalence of esophageal dysmotility in the globus GERD group was 33.3% and 23.3% in the typical GERD group.…”
Section: Discussionmentioning
confidence: 89%
“…Esophageal dysmotility may also contribute to GERD. Previous studies have shown a higher frequency of esophageal dysmotility in GERD with globus rather than GERD with typical symptoms (7)(8)(9). High-resolution manometry (HRM) is a useful tool in evaluating esophageal motility (10) and this study aimed to compare the esophageal motility between GERD patients with and without globus symptoms.…”
Section: Introductionmentioning
confidence: 98%
“…It has been demonstrated that HRM is a novel, promising technique that might be helpful in understanding the relationship between the esophageal motor parameters and GERD. 8,9,[21][22][23] The study herewith presented is hampered by some limitations. The small population of patients enrolled does not allow consideration of these conclusions as definitive.…”
Section: Discussionmentioning
confidence: 99%